Examining the barriers to sexual assault evidence processing in washington state: what’s the hold up? - Randol, Blake M. (Criminology, criminal justice, law & society, 2015)
Advances in forensic DNA technology have substantially increased the ability to deliver justice to victims and the wrongfully accused. The greatest challenge arising from this developing technology is the insufficient capacity of local criminal justice systems to process the escalating number of requests for biologicalevidence testing that has contributed to unprecedented and growing back logs in forensic DNA evidence processing throughout the United States. This study uses survey data collected from criminalinvestigators and prosecutors in Washington State to evaluate the predominate barriers that prevent the processing of biological evidence from unknown suspectsexual assault cases. Results show that a number of factors prevent the investigation of these stranger rape cases including resource constraints; anticipated delays and backlogs at state crime labs; lack of knowledge concerning the crime lab’s processes and priorities; and misconceptions concerning the efficacy of CODIS as an investigatory tool to identify unknown suspects.